2018
DOI: 10.1016/j.ijid.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

A waterborne outbreak of multiple diarrhoeagenic Escherichia coli infections associated with drinking water at a school camp

Abstract: This outbreak points to the importance of drinking water quality management in group facilities where underground water is used and emphasizes the need for periodic sanitation and inspection to prevent possible waterborne outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 21 publications
(23 reference statements)
5
35
0
3
Order By: Relevance
“…The presence of E. coli in the various water sources may spell health hazards such as diarrhoeal diseases which account for a substantial degree of morbidity and mortality in adults and children [20–24]. Control of diarrhoea may require the administration of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of E. coli in the various water sources may spell health hazards such as diarrhoeal diseases which account for a substantial degree of morbidity and mortality in adults and children [20–24]. Control of diarrhoea may require the administration of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…A case study in 2015 reported that 188 patients experienced acute gastrointestinal symptoms after school camp in Korea, wherein these symptoms were caused by diarrheagenic E. coli (DEC) in drinking water. After investigation, the research team indicated that damaged pipeline and inefficient water purification system for bacteria and virus were two primary reasons (Park et al, 2018). Another outbreak of norovirus gastroenteritis in Italy was associated with improper drinking water system caused by an old chlorination device and close proximity to suspected illegal sewage dumping (Giammanco et al, 2018).…”
Section: Occurrence Of Waterborne Pathogensmentioning
confidence: 99%
“…Enterotoxigenic E. coli (ETEC) is the most common serovar of E. coli and is commonly associated with foodborne diarrheal infections during traveling to endemic regions in Africa, Asia, and South America (Diemert 2006;Steffen 2017;Steffen et al 2015). Many studies have illustrated the role of ETEC and other diarrheagenic E. coli strains in the occurrence of diarrheal infections and the emergence of outbreaks in MGs through catering (Kim et al 2017;Ochi et al 2017;Park et al 2018). Approximately 33.3% of the E. coli-positive samples from symptomatic diarrheal cases at Hajj have been identified to contain bla CTX-M-15 and bla NDM genes that are associated with resistance to third-generation cephalosporins (Abd El Ghany et al 2017).…”
Section: Drug-resistant Enteric Infections At Hajjmentioning
confidence: 99%